2002
DOI: 10.1080/13504850210138469
|View full text |Cite
|
Sign up to set email alerts
|

The causality between female labour force participation and the availability of childcare

Abstract: It is typically found that the labour force participation of women is negatively affected by the presence of young children. This paper focuses on the causality, in the sense of Granger's definition, between the participation of mothers of young children and childcare provision. It is found that childcare Granger causes participation without feedback, which supports the claim that women could be constrained in their participation by the lack of childcare facilities. The absence of a feedback mechanism raises t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 10 publications
3
45
0
4
Order By: Relevance
“…They find that in Swedish regions without rationing the price mechanism applies, but not in regions with a lack of facilities. Chevalier and Viitanen (2002) conclude that in the UK a lack of childcare facilities limits female labor force participation. For Italy, Del Boca et al (2005) find that the price of childcare induces substitution between different forms of care, while the use of public childcare in Italy can increase substantially when the availability grows to a level comparable with northern European countries.…”
Section: Importance Of Economic Factorsmentioning
confidence: 96%
“…They find that in Swedish regions without rationing the price mechanism applies, but not in regions with a lack of facilities. Chevalier and Viitanen (2002) conclude that in the UK a lack of childcare facilities limits female labor force participation. For Italy, Del Boca et al (2005) find that the price of childcare induces substitution between different forms of care, while the use of public childcare in Italy can increase substantially when the availability grows to a level comparable with northern European countries.…”
Section: Importance Of Economic Factorsmentioning
confidence: 96%
“…In Germany private childcare providers are rare and public childcare provision -especially for children below three years of agedoes not meet demand (ibid.). In the UK, it is mainly the high costs of childcare that affect female labour supply (Chevalier and Viitanen, 2002). Not surprisingly then, attendance hours for British and German children are low: in 2005, for example, the average hours of attendance were 16 in the UK and 23 in Germany (OECD, 2012).…”
Section: Childcarementioning
confidence: 99%
“…Focusing on the observation that low labour market participation rates of married women are observed together with low birth rates in Italy, Del Boca (2002) empirically confirmed that the availability of childcare and part-time work increase both the probability of working and having a child; in contrast, Del Boca and Vuri (2007) identified that the lack of local availability and flexibility in the hours of childcare services limits women's participation in the full-time employment market. Chevalier and Viitanen (2002) found that the lack of childcare facilities limits the participation of women in the labour force by using a data from the UK. Focusing on the Japanese women's behaviour, targeted in this study, Raymo and Lim (2010) observed that despite improvements in women's educational attainment, expanding occupational opportunities, and passage of the Child Care Leave Law in 1992, there has been little change in the tendency to exit the labour force.…”
Section: Reviewmentioning
confidence: 99%